ANTISPERMATOGENIC ACTIVITY OF ETHANOLIC EXTRACT OF CALINA PAPAYA LEAVES ON SEMINIFEROUS TUBULES WISTAR RATS - Haris Setiawan; Sri Wijayanti Wulandari; Erlita Devi Agustina (Jurnal Kedokteran Hewan, 2021)
Indonesia is a country with high birth rate and the rate continues to increase each year. Methods to reduce high birth rate are needed, especially herbal based contraceptives. This research aims to study the possibility of Calina papaya leaf ethanolic extract as an antispermatogenic agent which hopefully could be expanded into natural antifertiliy drug candidate. Research was done using 24 white male Wistar rats divided into four groups. Dosages were given as follows: 0 mg/Kg W (control group), 100 mg/Kg W (P1), 200 mg/Kg W (P2) and 300 mg/Kg W (P3). Treatment was given in 30 days period. Rats were sacrificed on Day 31 and the testes were taken. Testes were then made into histological specimen using paraffin block and stained using Haematoxylin-Eosin. The diameter and surface area of seminiferous tubules, lumen surface area, and spermatogenesis index were then observed. Results showed that there is a significant difference (p0.05) on lumen surface area and spermatogenesis index between control and treatment groups. It is also found that the optimum dosage given to attain the desirable effect is 300 mg/Kg W. There is no significant difference found on surface area and diameter of tubulus seminiferous between control and treatment group (p0.05). Based on the results, papaya leaf (Calina variety) ethanolic extract has the potential a natural antispermatogenic with the optimum dose of 300 mg/Kg W.